Subcutaneous Ketamine in Depression: A Systematic Review - Cavenaghi, Vitor Breseghello; da Costa, Leandro Paulino; Lacerda, Acioly Luiz Tavares; Hirata, Edson Shiguemi; Miguel, Eurípedes Constantino; Fraguas, Renério (Frontiers in Psychiatry, 2021)
BACKGROUND: Ketamine has been shown to produce a rapid and robust antidepressant effect. Though numerous routes of administration have been studied, subcutaneous (SC) has proven to be a convenient and cost-effective route making its use particularly relevant in developing countries. Here we provide a systematic review covering the use of SC racemic ketamine and esketamine in depression, including its efficacy, safety and tolerability. METHODS: A systematic literature search was carried out, from inception through March, 2021,, using PubMed/MEDLINE, EMBASE and Web of Science, with no limits of language. After identifying 159 potentially relevant articles, 12 articles were selected after applying our inclusion/exclusion criteria. These comprised two randomized clinical trials, five case-reports and five retrospective studies. Given the small number of studies found and their heterogeneous nature, a meta-analysis was not considered appropriate. Here we provide a synthesis of these data including participant characteristics, dose range, efficacy, safety/tolerability. Risk of bias was accessed using the Cochrane risk of bias tool. RESULTS: SC Ketamine was administered to unipolar and bipolar patients a single dose, weekly or twice-weekly, a dose-titration approach was made in major studies, dose ranged from 0.1 to 0.5mg/Kg of racemic ketamine and 0.5 to 1mg/Kg of esketamine. Across all studies, SC ketamine showed a rapid and robust antidepressant effect, with response/ remission rates from 50-100% following both single or multiple doses, with transitory side effects. CONCLUSION: SC racemic ketamine and esketamine in depression is a promising strategy showing beneficial efficacy and tolerability. Future studies exploring the SC route, its cost-effectiveness, and a direct comparison with IV and intranasal (IN) protocols are warranted. PROSPERO Registration Number: CRD42019137434